Contours in Social Change: Elemental Graphics and a Surrogate Variable for Gamma Change - Golembiewski, Robert T. (Academy of Management Review, 1986)
This article illustrates the plural concept of change–alpha, beta, and gamma varieties. Socio-political and technical perspectives are employed to reinforce the significance of the concept. In addition, an analysis of a surface with cusp-like properties (a) helps visualize the three types of change; (b) elaborates the interpretive problems; and (c) suggests how the concept can have the inadvertent effect of contributing to a pessimistic view of research and intervention. Finally, a phase model of burn-out seeks to ameliorate this pessimism.